Apocynin loaded silver nanoparticles displays potent in vitro biological activities and mitigates pyrogallol-induced hepatotoxicity. (25th September 2022) - Ekozin, Adriel; Otuechere, Chiagoziem A.; Adewuyi, Adewale
Abstract: Drug-loaded nanoparticles are currently gaining attention due to their improved drug delivery properties. Apocynin, a natural polyphenolic compound, is a component of many plants. It has many medicinal and pharmacological properties. Pyrogallol is an anti-psoriatic agent. However, its clinical usage is limited due to its cumulative and dose-dependent hepatotoxicity. The objective of this study was to synthesize silver nanoparticles coated with Apocynin (Apo-AgNPs), and investigate the antioxidant and liver protective effects of Apo-AgNPs on pyrogallol-induced toxicity in rats. The nanoparticles were characterized and it was determined that the synthesis technique results in homogeneously dispersed core–shell Ag structures with spherical forms and an average diameter of 13 nm (6.3 nm). Our results showed that Apo-AgNPs exhibited potent antioxidant and excellent membrane stability activities in vitro. In rats, Apo-AgNPs (10 and 30 mg/kg) significantly prevented pyrogallol-induced elevations of alkaline phosphatase, gamma-glutamyl transferase, creatinine, urea, aspartate aminotransferase, alkaline aminotransferase, total bilirubin, and decreased blood levels of uric acid. Moreover, Apo-AgNPs restored the decreased activities of the liver antioxidant enzymes, including superoxide dismutase and glutathione peroxidase, glutathione transferase, as well as non-enzyme antioxidant glutathione, as well as significantly decreased catalase activities which were induced by pyrogallol treatment. Histological studies indicated that pyrogallol -induced liver damage was alleviated following Apo-AgNPs treatment in rats. Apo-AgNPs significantly suppressed the up-regulation of Cyclooxygenase-2 (COX-2), Interleukin 6 (IL-6) and Nuclear factor-κB (NF-κB) protein expression. These results indicated that Apo-AgNPs protected the rats from damage via preserving the antioxidant defense systems, lowering pro-inflammatory cytokines, and expression of COX-2 and NF-κB in rats. Highlights: A novel Apo-AgNPs was synthesized and characterized. Apo-AgNPs demonstrated significant antioxidant activities in vitro. Apo-AgNPs displayed protection to the liver upon pyrogallol induced hepatotoxicity. Apo-AgNPs exhibited inhibition to inflammatoin upon pyrogallol induced toxicity.